Survival in patients with chronic thromboembolic pulmonary hypertension treated with riociguat versus other medications: a COMPERA analysis - Held, Matthias; Pausch, Christine; Huscher, Doerte; Pittrow, David; Halank, Michael; Beckmann, Stephan; Stadler, Stefan; Tello, Khodr; Grünig, Ekkehard; Opitz, Christian; Delcroix, Marion; Ghofrani, H. Ardeschir; et al. (ERJ Open Research, 2025)
Extract: Current treatment options for patients with chronic thromboembolic pulmonary hypertension (CTEPH) include surgical pulmonary endarterectomy (PEA), interventional balloon pulmonary angioplasty (BPA) and medical therapy [1, 2]. For many years, medical treatment primarily involved off-label use of drugs approved for pulmonary arterial hypertension, despite limited and sometimes inconclusive evidence supporting their effectiveness in CTEPH patients. In 2014, riociguat, a soluble guanylate cyclase stimulator, became the first drug approved for treating patients with inoperable CTEPH or persistent/recurrent pulmonary hypertension (PH) post-surgery [3]. Parenteral treprostinil was subsequently approved for CTEPH [4], although its use has remained limited, likely due to the invasiveness and associated side-effects.
Online veröffentlicht: 8. Dezember 2025
Gesehen am 20.02.2026